'Tis the season to be busy…. (2nd December 2019) - Hussain, Corrine
Abstract : As Christmas fast approaches, aesthetic clinics begin to fill with patients seeking treatments to ensure they are looking their best over the holiday season. Corrine Hussain details how clinics can make the most out of their business, while also touching on the BACN's annual conference held last month